Microbial polyphenol oxidases in tea catechin oxidation: A novel approach to tea biotransformation - Muthulingam P; Rashidinejad A; Popovich D; Punyasiri PAN; Nanayakkara CM; Mesarich CH (Elsevier Ltd on behalf of the Institution of Chemical Engineers, 2025)
Black tea processing is a complex biochemical process influenced by both plant-derived and microbial enzymes, during which catechins undergo enzymatic oxidation to form compounds such as theaflavins and thearubigins - key contributors to tea's colour, flavour, and health benefits. While endogenous polyphenol oxidases have traditionally been regarded as the primary agents of catechin oxidation, emerging evidence highlights the significant role of bacterial species in modulating tea quality through enzymatic transformations. In this study, bacterial communities were isolated from various stages of black tea processing and screened for extracellular polyphenol oxidase (PPO) activity. Among 43 isolates, Alcaligenes faecalis exhibited the highest PPO activity. Enzyme profiling of A. faecalis revealed peak laccase and catechol oxidase activities at 36 h (12.6 U/mL and 3.6 U/mL, respectively), while peroxidase activity peaked earlier at 24 h (4.2 U/mL) in nutrient broth. High-performance liquid chromatography (HPLC) analysis showed a concentration-dependent decline in epigallocatechin gallate (EGCG) from 816.24 mg/L to 333.33 mg/L, accompanied by the formation of gallic acid (up to 29.81 mg/L), epigallocatechin, gallocatechin, gallocatechin gallate, and tea pigments. These results confirm the enzymatic degradation and transformation of EGCG into key tea polyphenols, closely mimicking traditional black tea oxidation. A proposed bioconversion pathway outlines the microbial transformation of EGCG into tea pigments. These findings demonstrate the functional contribution of tea-processing-associated bacteria and propose microbial enzymes as a novel biocatalytic tool to enhance black tea fermentation and improve product quality. Future research should focus on enzyme purification and industrial scalability to integrate microbial biotransformation into tea production.
Keywords: Alcaligenes faecalis; EGCG; Microbial biotransformation; Polyphenol oxidase; Tea oxidation; Theaflavins